The Efficacy and Safety of Insulin Degludec Given in Variable Once-Daily Dosing Intervals Compared With Insulin Glargine and Insulin Degludec Dosed at the Same Time Daily: A 26-week, randomized, open-label, parallel-group, treat-to-target trial in individuals with type 2 diabetes - Meneghini, Luigi (American Diabetes Association, 2013)
OBJECTIVE: The requirement to inject current basal insulin analogs at a fixed time each day may complicate adherence and compromise glycemic control. This trial evaluated the efficacy and safety of varying the daily injection time of insulin degludec (IDeg), an ultra-long-acting basal insulin. RESEARCH DESIGN AND METHODS: This 26-week, open-label, treat-to-target trial enrolled adults (≥18 years) with type 2 diabetes who were either insulin naïve and receiving oral antidiabetic drugs (OADs) (HbA(1c) = 7–11%) or previously on basal insulin ± OAD(s) (HbA(1c) = 7–10%). Participants were randomized to 1) once-daily (OD) IDeg in a prespecified dosing schedule, creating 8–40-h intervals between injections (IDeg OD Flex; n = 229); 2) once-daily IDeg at the main evening meal (IDeg OD; n = 228); or 3) once-daily insulin glargine at the same time each day (IGlar OD; n = 230). The primary outcome was noninferiority of IDeg OD Flex to IGlar OD in HbA(1c) reduction after 26 weeks. RESULTS: After 26 weeks, IDeg OD Flex, IDeg OD, and IGlar OD improved HbA(1c) by 1.28, 1.07, and 1.26% points, respectively (estimated treatment difference [IDeg OD Flex − IGlar OD]: 0.04% points [–0.12 to 0.20], confirming noninferiority). No statistically significant differences in overall or nocturnal hypoglycemia were found between IDeg OD Flex and IGlar OD. Comparable glycemic control and rates of hypoglycemia were seen with IDeg OD Flex and IDeg OD. Adverse event profiles were similar across groups. CONCLUSIONS: The use of extreme dosing intervals of 8–40 h demonstrates that the daily injection time of IDeg can be varied without compromising glycemic control or safety.